1985
DOI: 10.1203/00006450-198502000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Laser Investigation of Bilirubin-Photobilirubin Photoconversion

Abstract: The reversibility of the configurational photoisomerization process of bilirubin (BR) with laser lines in the blue-green spectral region is investigated. Photoisomerization efficiency of BR is found to depend strongly on wavelength, and to decrease when the excitation wavelength is increased from blue to green. Reversion of BR photoisomers (identical to photobilirubin, PBR) back to native BR is demonstrated for several laser lines by irradiating PBR/BR mixtures with wavelengths greater than the excitation wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Earlier studies suggested that the increased bilirubin photodegradation at the higher wavelengths is mainly due to an increase in lumirubin formation, [24][25][26] which was found to be more rapidly excreted in vivo 6,7,27,28 in contrast to the geometric E,Zand Z,E-isomers that could be converted back to the Z,Z-isomer. 29 Since the E,Zand Z,E-configurational isomers are also diazopositive, 10 our determination of the amount of remaining bilirubin after light exposure use of the diazo method mainly reflects the conversion of bilirubin to lumirubin, which is diazo-negative.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies suggested that the increased bilirubin photodegradation at the higher wavelengths is mainly due to an increase in lumirubin formation, [24][25][26] which was found to be more rapidly excreted in vivo 6,7,27,28 in contrast to the geometric E,Zand Z,E-isomers that could be converted back to the Z,Z-isomer. 29 Since the E,Zand Z,E-configurational isomers are also diazopositive, 10 our determination of the amount of remaining bilirubin after light exposure use of the diazo method mainly reflects the conversion of bilirubin to lumirubin, which is diazo-negative.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies in vitro showing that light of wavelengths between 350 and 450 nm is mutagenic for prokaryotic and eukaryotic cells, and therefore potentially carcinogenic, have caused concern because all commonly-used phototherapy lamps emit radiation in this region. Furthermore, a greater efficacy of green lamps compared with white fluxorescent lamps has been reported (Vecchi et al, 1982;Pratesi, 1983;Pratesi et al, 1985). As a possible cause for this Donzelli et al (I1984) suggest that the green light penetrates deeper into the skin, and the best spectral range for efficient photodegradation of bilirubin may be the result of a balance between bilirubin absorption and skin penetration.…”
Section: Resultsmentioning
confidence: 98%
“…Symbols: 0, (EZ)-bilirubin; *, sible for the rapid biliary and urinary clearance ofbilirubin during phototherapy (Onishi et al, 1980b, 198 1a;Castarino et al, 1985;McDonagh & Lightner, 1985). (EZ)-Cyclobilirubin, as photoreversible structural isomers of bilirubin (Isobe & Onishi, 1981), though many authors have described it as 'non-reversible' (Castarino et al, 1985;Knox et al, 1985;Pratesi et al, 1985), attains much lower serum concentrations, but is more rapidly excreted. Thus structural isomerization, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the isomers have overlapping absorption spectra, a photoequilibrium state is achieved when bilirubin is irradiated under anaerobic conditions. When bilirubin is bound to human albumin, there is a marked wavelength dependence for the equilibrium between native bilirubin and the 4Z,15E-isomer (Ennever et al, 1983;Pratesi et al, 1984aPratesi et al, , 1985Onishi et al, 1986a;Itoh et al, 1987). Pratesi et al (1984a) have fit experimental data on the isomer composition at photoequilibrium to a simple kinetic model which assumes a common twisted intermediate between 42,152 and 4Z,15E (Greene et al,198l), to determine the relative quantum yield for the two reactions.…”
Section: Configurational Isomerizationmentioning
confidence: 99%